2017
DOI: 10.1111/asj.12934
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol levels of lactating dairy cows in cold‐ and warm‐temperate regions in Japan

Abstract: We compared the hair cortisol levels of lactating dairy cows in a cold- and a warm-temperate region out of four climatic zones in Japan. We simultaneously investigated the effects of calving number, lactation period and month of hair sampling. Hair of nine Holstein lactating cows chosen from each region (i.e. 18 cows per sampling) was sampled in March, June, September and December. Number of calvings (1, 2, ≥3) and lactation duration (early: <100, middle: 101-200, and late: >201 days) were balanced between reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…Therefore, it is pivotal to establish a nutritional strategy that helps to minimize the impaired productivity of beef cattle due to temperature conditions. Cold stress causes negative effects on growth performance and immune cell population by influencing metabolic and immunological activities [5,6]. Thus, hematological profiles, if measured, could be a good indicator of how stressors affect the immune function of the body [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is pivotal to establish a nutritional strategy that helps to minimize the impaired productivity of beef cattle due to temperature conditions. Cold stress causes negative effects on growth performance and immune cell population by influencing metabolic and immunological activities [5,6]. Thus, hematological profiles, if measured, could be a good indicator of how stressors affect the immune function of the body [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Cold stress causes negative effects on growth performance and immune cell population by influencing metabolic and immunological activities [5,6]. Thus, hematological profiles, if measured, could be a good indicator of how stressors affect the immune function of the body [6][7][8][9]. The thermo-neutral zone for growing Korean native beef cattle is approximately 4 to 20 • C, and the critical temperature is approximately −10 • C [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair CORT has been shown to vary throughout the year. One study of Holstein cows found that June was associated with the highest CORT levels (13.0 ± 1.0 pg/mg, n = 18) [38], while another assessing Swiss dairy breeds identified winter as the season with the highest CORT levels (0.86 ± 0.37 pg/mg, n = 27) [11] (see Supplementary Figure S2 for comparisons). Our data agreed with the former rather than the latter, which may be linked to the maximum THI for July reaching 75.…”
Section: Hair Cortisol Analysesmentioning
confidence: 99%
“…Without multiple years being analysed, it is hard to confirm which factor caused the increase in hair CORT in the August session. If this change truly is seasonal, then this increase may not be associated with AMS and could be linked to heat stress, increased walking or changes to feeding method [30,32,38].…”
Section: Hair Cortisol Analysesmentioning
confidence: 99%